ANALISIS KONFLIK SOSIAL DALAM DRAMA MEGA-MEGA KARYA ARIFIN C. NOER: KAJIAN SOSIOLOGI SASTRA - Azzahrah, Erlin Atifah; Mustika, Anggun Fatma; Hasanah, Maulinda Nurul; Ningsih, Ika Rahayu Nursulistya; Azzahro, Firlanda (Bahtera Indonesia, 2026)
This study aims to analyze the representation of social conflict in the play Mega-Mega by Arifin C. Noer using a sociological approach to literature. The drama portrays various forms of social conflict, such as injustice, structural poverty, marginalization, gender inequality, and the breakdown of humanitarian values. Ian Watt’s theory of the sociology of literature is employed to explore the relationship between social reality and the content of the literary work, as well as how literature serves as a mirror and critique of societal conditions. This research adopts a qualitative descriptive method with content analysis techniques. The findings reveal that Mega-Mega functions not only as a medium of entertainment but also as a powerful tool of social criticism against inequality and injustice. Values such as the struggle for life, social awareness, and hope are depicted through characters living under social and economic pressure. This study contributes to the enrichment of literary sociology by demonstrating how literature reflects and gives voice to complex social realities. Keywords: Sociology of literature, social conflict, Mega-Mega drama, Arifin C. Noer, social inequality, social criticism.